1998
DOI: 10.1016/s0266-7681(98)80174-5
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Audit of Hand and Wrist Injuries

Abstract: This study reports the characteristics, causes and disposal of isolated injuries to the hand and wrist presenting to six accident and emergency departments over a period of 4 months. The rate of isolated injury to the hand or wrist was 6.6%. The male: female ratio was 2.2: 1, with the mean age for injury being 26.4 years in men and 29.2 years in women. The modal age group for injury was 21-25 years in men and 11-15 years in women. The right and left hand were injured almost equally. The dominant hand was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
66
5
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 11 publications
10
66
5
2
Order By: Relevance
“…Our study was in contrast to the study by Niemines et al' [7] which showed 70 % of adult hand injuries occurring at home, 28 % at work, and 3 % in road accidents, which in our study was 13.6 % at home, 26.2 % at work, 27.1 % assault, and 13.9 % road accidents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study was in contrast to the study by Niemines et al' [7] which showed 70 % of adult hand injuries occurring at home, 28 % at work, and 3 % in road accidents, which in our study was 13.6 % at home, 26.2 % at work, 27.1 % assault, and 13.9 % road accidents.…”
Section: Discussioncontrasting
confidence: 99%
“…Hand injuries demonstrated a peak in the age group of 21-35 years influenced primarily by industrial accidents and altercations. In our study, the number of hand injury cases in 1-5 years age group was 6.8 % of all cases, which is high when compared to 4.2 % in a study done in North Ireland [7]. The incidence of young Swedish children with hand injuries referred for treatment is 27/10,000 children/year.…”
Section: Discussioncontrasting
confidence: 51%
“…Physiotherapy must be systematic and constantly supervised by the hand surgeon with application of multi modality approach. From the industry point of view adequate breaks, recreation facilities, counseling team should be provided [15]. On occurrence of injury appropriate first aid, transport, emotional support, adequate rehabilitation and compensation go a long way in gaining confidence of workers.…”
Section: Discussionmentioning
confidence: 99%
“…[8,[12][13][14] The dominant hand was seen to be the most injured. In our study, right hand injuries occured more commonly.…”
Section: Discussionmentioning
confidence: 99%